Absolute Quantitative MALDI Imaging Mass Spectrometry: A Case of Rifampicin in Liver Tissues - Chumbley, Chad W; Reyzer, Michelle L; Allen, Jamie L; Marriner, Gwendolyn A; Via, Laura E; Barry, 3rd, Clifton E; Caprioli, Richard M (Analytical chemistry (Washington), 2016)
Matrix-assisted laser desorption/ionization (MALDI) imaging mass spectrometry (IMS) elucidates molecular distributions in thin tissue sections. Absolute pixel-to-pixel quantitation has remained a challenge, primarily lacking validation of the appropriate analytical methods. In the present work, isotopically labeled internal standards are applied to tissue sections to maximize quantitative reproducibility and yield accurate quantitative results. We have developed a tissue model for rifampicin (RIF), an antibiotic used to treat tuberculosis, and have tested different methods of applying an isotopically labeled internal standard for MALDI IMS analysis. The application of the standard and subsequently the matrix onto tissue sections resulted in quantitation that was not statistically significantly different from results obtained using HPLC-MS/MS of tissue extracts. Quantitative IMS experiments were performed on liver tissue from an animal dosed in vivo. Each microspot in the quantitative images measures the local concentration of RIF in the thin tissue section. Lower concentrations were detected from the blood vessels and around the portal tracts. The quantitative values obtained from these measurements were comparable (>90% similarity) to HPLC-MS/MS results obtained from extracts of the same tissue.